Literatur Review: Dampak konsumsi tempe terhadap modulasi sistem imun dalam meningkatkan IgA, menurunkan IgE, dan IL-6 - Putrianty, Nadhira Rifani; Octaria, Yessi Crosita (Poltekkes Kemenkes Aceh, 2024)
Background: Cases related to the immune system, such as infections, tend to increase because human life heavily depends on the activation and supression of immune responses to combat various pathogens and disease factors. The nutritional content of tempeh is known to have the ability to regulate the immune system, either enhacing ot inhibiting immune responses.Objectives: This study aimed to determine the impact of consuming tempeh on immune system modulation specifically in increasing IgA, decreasing IgE and IL-6.Methods: The type of research is a narrative review that uitilzes articles from 2014 to 2024, sourced from Google Scholar, PubMed, and ScienceDirect. The reviewed articles were quasi-experimental and experimental studies on humans and animal models. Inclusion and exclusion criteria were guided by the PICOS framework. Data were processed and analyzed using the PRISMA approach to filter and identify relevant literature, followed by a narrative synthesis to interpret research findings.Results: Tempeh consumption induces an increase in IgA production, reduces IgE levels, and lowers IL-6 concentrations. IgA secretion increased from 2098 ng/mL to 2573 ng/mL in males and from 2376 ng/mL to 2421 ng/mL in females after 25 days of tempeh intake. Combining tempeh consumption with resistance training for 2 weeks also elevated sIgA concentrations from 70.123 ng/mL to 77.216 ng/mL. In rats, tempeh Rs reduced plasma IgE levels from 1.2 µg/mL to 0.8 µg/mL after 14 days and decreased skin severity scores from 2.5 to 1.5. Conclusion: Tempeh consumption positively influences immune modulation by increasing IgA levels, reducing IgE, and lowering IL-6 concentrations.